2012
DOI: 10.1155/2012/892706
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase 4 Inhibition May Facilitate Healing of Chronic Foot Ulcers in Patients with Type 2 Diabetes

Abstract: The pathophysiology of chronic diabetic ulcers is complex and still incompletely understood, both micro- and macroangiopathy strongly contribute to the development and delayed healing of diabetic wounds, through an impaired tissue feeding and response to ischemia. With adequate treatment, some ulcers may last only weeks; however, many ulcers are difficult to treat and may last months, in certain cases years; 19–35% of ulcers are reported as nonhealing. As no efficient therapy is available, it is a high priorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 32 publications
1
62
2
2
Order By: Relevance
“…Approximately 15% of diabetic patients are affected by a diabetic foot ulcer. It is a major health problem since it causes pain, suffering and poor life quality [7].…”
Section: Complications Of Diabetesmentioning
confidence: 99%
See 3 more Smart Citations
“…Approximately 15% of diabetic patients are affected by a diabetic foot ulcer. It is a major health problem since it causes pain, suffering and poor life quality [7].…”
Section: Complications Of Diabetesmentioning
confidence: 99%
“…Its role in the regulation of cell adhesion, migration, apoptosis, angiogenesis and extracellular matrix degradation was previously confirmed. It was indicated that DPP IV/ CD26 plays a particularly relevant role in tissue regeneration where it was found to influence inflammatory processes and impacts the process of epithelialization of wounds [6,7,10].…”
Section: Dipeptidyl Peptidase Iv/molecule Cd26 (Dpp Iv/ Cd26)mentioning
confidence: 99%
See 2 more Smart Citations
“…(Gross & Nehme, 1999;Caiafa et al, 2011). Pacientes com história prévia de úlcera ou amputação têm elevado risco para o desenvolvimento de novas úlceras, infecção e gangrena, podendo culminar em amputação (Milman et al, 2001;Bortoletto et al, 2009;Marfella et al, 2012).…”
Section: Introductionunclassified